Gross regional product as the indicator of differentiation of social-economic development of the regions (Russia in transition) - Alexander Granberg; Irina Masakova; Ioulia Zaitseva (European Regional Science Association (ERSA), 1998)
Gross regional product (GRP) becomes the main indicator of social-economic development of the region in conditions of transition of Russian statistics to the system of national accounts (SNA). Data GRP per capita are analyzed for 89 regions of Russia. In 1995 differentiation of GRP per capita made up almost 18 times (according to unofficial data - much more). The following guestions are discussed: ? specification of GRP estimation methods; ? value and material structure of GRP; ? factors of GRP per capita differentiation and relevant typologies of the regions; ? linkages between GRP and other macro-indexes of the regions. In the paper are given estimation of the implementation of the regional policy goals (bring together of the regions from GRP per capita, etc.).
Keywords: 330